The tiger's apprentice - Yep, Laurence, 1948- (Yep, Laurence, 1948- Tiger's apprentice, 2021)
A tiger, a monkey, a dragon, and a twelve-year-old Chinese American boy fight to keep a magic talisman out of the hands of an enemy who would use its power to destroy the world.